Assessment of Antibacterial, Antioxidant & Anti-inflammatory Activities and Phytochemical Screening of Typha elephantina Roxb. (Hogla) Leaves (Bangladesh Pharmaceutical Journal, 2025)
Typha elephantina Roxb, locally known as ‘Hogla’ in Bangladesh, is widely found in wet areas. In this work, T. elephantina leaves were used for developing the methanolic crude extract, which afterwards went through antibacterial, antioxidant and anti-inflammatory assays in addition to phytochemical investigations. Alkaloids, carbohydrates, tannins, phenolics, carbohydrates and flavonoids were identified in the extract. The methanolic extract of the leaves of T. elephantina revealed the highest level of antibacterial activity against E. coli. It exhibited an IC50 of 42.02 μg/ml in the DPPH free radical scavenging assay. The total phenolic content (TPC) of it was 29.96 milligrams of gallic acid equivalents (GAE) per gram of test extract. In the anti-inflammatory assay, the extract reduced paw edema 28.8% (p < 0.05) and 38.83% (p < 0.01) in the third and fourth hours of carrageenan administration. Taken together, the leaves of T. elephantina might be considered biologically active.Bangladesh Pharmaceutical Journal 28(1): 56-62, 2025 (January)